Retail Purchases of Red and Processed Meat by State in the United States. (13th December 2022) - Semba, Richard D.; Ramsing, Rebecca; Thorne-Lyman, Andrew L.; Rahman, Nihaal; Altema-Johnson, Daphene; Chang, Kenjin B.; Young, Ruth; Nussbaumer, Elizabeth; Bloem, Martin W.; Love, David
Abstract: The specific aim was to characterize retail purchases of red and processed meat and other major protein-rich foods in the U.S. and by state. Supermarket scanner data from grocery stores, supermarkets, and big box stores collected from 2017-2019 (NielsenIQ, New York, NY) was used to characterize retail purchases of red meat, processed meat, and other protein-rich foods in thirty-one states representative of US retail food sales. Red meat, processed meat, poultry, seafood, eggs, other meats, and non-meat foods (beans, nuts, seeds, meat alternatives) by weight accounted for 25.9%, 20.4%, 25.8%, 5.9%, 12.6%, 1.3%, and 10.1%, respectively of total sales in 2017-2019. Mean per capita purchases of red meat by weight was 30.1 g/d, ranging from 45.4 g/d in Mississippi to 21.9 g/d in New York. Mean per capita purchases of processed meat by weight was 23.8 g/d, ranging from 36.6 g/d in Mississippi to 15.2 g/d in California. We observed statistically significant correlations between red and processed meat purchases with cardiovascular mortality and colorectal cancer by state. Per capita retail purchases of red and processed meat appear to reflect a dietary pattern that is not consistent with current national and international dietary recommendations.